La integración europea en la política de I+D: el espacio europeo de investigación, la resiliencia de un proyecto en constante evolución - ANA ARIZAGA BATIZ (Revista Vasca de Administración Pública, 2022)
The political project of creating a European Research Area (ERA),conceived as an internal knowledge market in which the free circulation ofresearchers, knowledge and technologies materializes, has historically inspiredthe deployment of European research and technological development policy.In fact, it constitutes its most ambitious vision, aimed at a true integration ofEuropean research. It is, however, a very ambitious objective that has progressedhesitantly and there is still a long way to go to achieve its completion and optimalfunctioning. The ERA, despite everything, continues to constitute the theoreticaland political framework that drives this European integration in the R&D sector,thanks to its ability to reinvent itself in the light of successive European politicalagendas and, in this decade 2021-2030, maintains its leading role as a tool at theservice of the Union¿s current challenges.